Prediction of Density and Viscosity of Biodiesel Fuel from Fatty Acid Methyl Ester (FAME) Composition - Jekayinfa, S.O.; Adebayo, A.O.; Sulaiman, M. A.; Ayoola, V.O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Viscosity and density are important properties that qualify biodiesel fuel to serve as an alternative fuel because all other properties directly or indirectly depend on them. The processes involved in determining the viscosity and density of biodiesel are relatively simple and costly and there are discrepancies in the results obtained due to the differences in the oil composition of the feed-stocks used as against the reported cause of experimental errors. This work aimed at theoretically determining and developing relationship between the density and viscosity of different feed-stocks and the fatty acid methyl ester composition at different temperatures.In the study, density and viscosity data of biodiesel fuels and the composition of FAME were collected from literatures. A linear regression analysis was carried out for density and viscosity on the average values of viscosity and density data obtained at different temperatures range (10°C-40°C) of FAME composition. Equations relating density and viscosity with the percentage composition by weight of FAME of biodiesel fuel were developed. Predicted mean values for kinematic viscosity and density were respectively between 4.31 - 5.64 mm2/s and 861.67 – 885.66 kg/m3. The developed equations were able to predict with up to 97.1% accuracy for viscosity and 98.5% accuracy for density. The developed equations could effectively predict the quality of biodiesel (viscosity and density) from various feedstocks based on FAME compositions.